THE DISTRIBUTION OF THE FIRST PERSON POSSESSOR VARIATIONS IN MADURESE GEOGRAPHIC AND SOCIAL DIALECT - Tunggul Puji Lestari; Ika Nurhayani (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2015)
Madurese has two types of first person possessive construction, the first person possessive markers, tang and sang and the definite suffix –na. This research aims at investigating the distribution of the Madurese first person possessor variations spoken in Madura island within the scope of geographic and social dialect. Madura island has four regencies, Bangkalan, Sampang, Pamekasan, and Sumenep regency. Although Sumenep is considered as the cultural capital of Madura, each regency in Madura has its own political institution and various local influences. In terms of language, each regencies has its own dialect. The research relies on descriptive qualitative research with questionnaire as its main instrument. The findings shows that distribution of the Madurese first person possessor variation is governed by geographic and social factors. Geographically, tang/sang construction is used in Bangkalan and Eastern Sampang regency while the definite suffix –na construction is used in Western Sampang, Pamekasan and Sumenep regency. Based on social dialect, the tang/sang construction is mostly used for the low level while the definite suffix na- is used for the middle and high speech levels.Key words: possessive, madura, mamdurase, social dialect